Corporate Governance and Integrated Reporting: A Systematic Review of Empirical Evidence in Business Contexts - Hidayat, Wahyudi Nur; Yusnaini Yusnaini (Yayasan Sinergi Kawula Muda, 2026)
This study investigates how corporate governance (CG) mechanisms influence the quality of integrated reporting (IR) by conducting a systematic review of 23 empirical articles published between 2020 and 2025, sourced from Sinta 4-accredited or Scopus Q4-indexed journals. The articles were selected using predefined inclusion criteria and analyzed thematically. The findings show that governance factors such as board independence, audit committee activity, board size, gender diversity, audit quality, and executive compensation play a significant role in enhancing IR quality. In Indonesia and other regions such as Asia, Europe, and South Africa, the influence of CG on IR is evident, although variations exist due to sectoral and methodological differences. Most studies are grounded in agency theory, with support from stakeholder and legitimacy theories. The review highlights that robust governance practices are consistently associated with high-quality integrated reporting, offering actionable insights for regulators, policymakers, and organizations aiming to strengthen CG frameworks and reporting practices.